Contribution of Word Reading Speed to Reading Comprehension in Brazilian Children: Does Speed Matter to the Comprehension Model? - Seabra, Alessandra G.; Dias, Natália M.; Mecca, Tatiana; Macedo, Elizeu C. (Frontiers in Psychology, 2017)
Studies have suggested that reading speed (RS) or fluency should be a component of reading comprehension models. There is also evidence of a relationship between RS and reading comprehension. However, some questions remain to be explored, as the changes in such a relationship may be a function of development. In addition, while there are studies published with English speakers and learners, less evidence exists in more transparent orthographies, such as Portuguese. This study investigated the relationship between reading comprehension and RS in typical readers. Objectives included elucidating the following: 1) the contribution of RS to reading comprehension controlling for intelligence, word recognition, and listening and 2) the differential relationships and contributions of RS to comprehension in different school grades. The sample of participants comprised 212 students (M = 8.76; SD = 1.06) from 2nd to 4th grade. We assessed intelligence, word recognition, word RS, listening, and reading comprehension. Performance in all tests increased as a function of grade. There were significant connections between reading comprehension and all other measures. Nonetheless, the regression analysis revealed that word RS has a unique contribution to reading comprehension after controlling for intelligence, word recognition, and listening, with a very modest but significant improvement in the explanatory power of the model. We found a significant relationship between RS and reading comprehension only for 4th grade and such relationship becomes marginal after controlling for word recognition. The findings suggest that RS could contribute to reading comprehension in Portuguese beyond the variance shared with listening and, mainly, word recognition, but such a contribution was very small. The data also reveal a differential relationship between RS and reading comprehension in different school grades; specifically, only for the 4th grade does RS begins to relate to reading comprehension. The findings add a developmental perspective to the study of reading models.